Incorporating immunohistochemical markers into screening methods for BRCA1-mutated breast cancer - Tuzimek, Agnieszka; Fudalej, Marta; Sobiborowicz, Aleksandra; Budzik, Michał; Badowska-Kozakiewicz, Anna (Polish Journal of Pathology, 2020)
BRCA1-mutated breast cancer (BC) is responsible for approximately 25% of hereditary breast cancer cases. BRCA1 is a tumor suppressor protein regulating the cell cycle and DNA repair; therefore its dysfunctions play a significant role in carcinogenesis. BRCA1-mutated BC is associated with basal-like phenotype, lack of expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) in addition to frequent TP53 mutations and poor prognosis. Currently used criteria for genetic evaluation of BC for the risk of hereditary mutations are based on patients’ age and family history, and therefore are prone to be imprecise or incomplete. This review discusses recently developed sets of immunohistochemical markers, promising independent markers (nestin, ALDH1, FOXO3, claudins, topoisomerase 1, EGFR) and their potential to be incorporated into clinical practice as a support tool in oncological counseling. This approach could be applied as a screening method for cost-effective selection of cases requiring genetic testing or adapted in pathology laboratories with limited access to molecular techniques. Although not all of the described predictor models have been validated yet, they could further improve the performance of BRCA1 screening methods in BC in the near future via increasing the accuracy of criteria for further genetic evaluation.